Laparoscopic Gastropexy Using Knotless Unidirectional Suture and an Articulated Endoscopic Suturing Device: Seven Cases. Issue 8 (12th October 2016) - Coleman, Kristin A.; Adams, Sean; Smeak, Daniel D.; Monnet, Eric
Abstract : Objective: To describe a technique for laparoscopic incisional gastropexy using an articulated endoscopic suturing device with knotless unidirectional barbed suture in healthy large breed dogs. Study Design: Prospective case series. Animals: Healthy client‐owned dogs presented for prophylactic gastropexy and weighing >20 kg (n=7). Methods: Incisional gastropexy was performed using a single port access system with an articulated endoscopic suturing device. An additional 5 mm cannula was placed in the right caudal abdomen. A 2‐0 knotless unidirectional barbed suture was used to complete the gastropexy with 2 separate simple continuous suture lines. All dogs underwent a focal abdominal ultrasound to evaluate the gastropexy site 3–12 months postoperatively. Results: Median weight of the dogs was 33.5 kg (range, 20–51 kg) and the median age was 2 years (range, 0.6–8.5 years). Medians urgical time was 60 minutes (range, 39–88). The articulated suturing device malfunctioned twice. On abdominal ultrasound between 3 and 12 months, all gastropexy sites were intact. No motion was detected between the stomach and body wall during distal antral contractions or respiratory motion and a focal thickening of the gastric wall was present in dog. No complications were reported in the postoperative periods as of the 2 week suture removal visit or as of the time of their ultrasound appointment. Conclusion: This technique using an endoscopic articulated suturing device with a knotless unidirectional barbed suture provides a feasible technique to perform laparoscopic gastropexy.